Health and the environment in peninsular Malaysia: geographical variation and imperatives - Asmah Ahmad, (Environmental Management Society, Malaysia, 2001)
This paper attempts to show the association of health status and environmental conditions. The former is measured in terms of infant mortality rate and crude death rate whilst the latter in terms of accessibility to water supply and adequate sanitation, household size, level of urbanization, road density and number of motorized vehicles per 10,000 population. The utilization of these variables as explanatory factors for health is carried out as strong relationship are found to exist between health and urban structure, since the incidence of many diseases is dependent upon population density, sanitation and environmental quality. When these associations were applied spatially, a pattern of geographical variation from among the states in Peninsular Malaysia was revealed. States with relatively better health status are those that were found enjoying relatively higher accessibility to water supply and adequate sanitation, smaller household size and lower degree of urbanization or, in other words, better environmental quality